(untitled) (Advances in Oceanography and Limnology, 2017)
This work allowed the comparison of the metabolic profiles of the most important cyanobacteria species in southern perialpine lakes, namely Aphanizomenon flos-aquae, Dolichospermum lemmermannii, Microcystis aeruginosa, Planktothrix rubescens, and Tychonema bourrellyi. Monospecific cultures were obtained from samples of 3 different natural lakes (Garda, Idro, and Caldonazzo). LC-MS/MS analyses were conducted on strains. A first set of experiments was aimed at assessing the presence of the best known toxins (microcystins, nodularins, (homo)anatoxin-a, cylindrospermopsins, paralytic shellfish poisons) in the cultures. Results of this screening study revealed that M. aeruginosa and P. rubescens produced toxic peptides (microcystins), T. bourrellyi produced toxic alkaloids (anatoxin-a and possibly some paralytic shellfish toxins), Aph. flos-aquae and D. lemmermannii did not produce any of the analyzed toxins. M. aeruginosa and P. rubescens showed typical microcystin production with LR form dominant in the former, and RRdm form dominant in the latter. A second set of experiments was aimed at comparing the capability of the 5 cyanobacterial species to produce peptidic secondary metabolites. For this purpose, an untargeted peptidomic analysis was conducted on the strains. The analysis allowed revealing globally 328 metabolites, spanning in a mass range between 400 and 2000 Da. The majority of compounds with masses in the 500-1200 Da range (corresponding to the majority of peptidic secondary metabolites) resulted to be produced by M. aeruginosa and P. rubescens strains, thus indicating a higher ability of these species to produce non-ribosomal peptides compared to the others. 27 metabolites out of 328 could be putatively assigned to specific classes of compounds: microcystins, aeruginosins and anabaenopeptins were the most represented classes of compounds, and were mostly found in M. aeruginosa and P. rubescens strains.